The Roman Byzantine Kharag, narrated by Ibn Khordadb - Al-Dulaimi, Muhammad Hassan Suhail (Journal of Humanities & Social Sciences, 2022)
The research dealt with the Kharaj of the Romans by the Byzantines in the third AH / ninth century AD with the narration of the Muslim country Ibn Khardathbe in his book Al-Masalik and the Mamalik, in which he talked about the Kharaj of the Romans in Asia Minor, and his source in that was the book (The News of the Romans and their Kings and Their Countries) and its author, Muslim Al-Jurimi, The Scientist in Countries Rum, as well as Presidency of the Office of Post and News The descriptive analytical approach based on explaining the novel was followed with its main elements (type of Kharaj, amount of Kharaj, times of Kharaj collection, incision of rum Kharaj).